Screen Time pada Pembelajaran Daring untuk Anak Usia Dini: Sejauh Mana Dampaknya? [Screen Time in Online Learning for Early Childhood: What Impact Does It Have?] - Wijono, Silviana; Tulung, Casey Rebecca; Jilly Shinta Desiree; Manalu, Tania Theresia (Jurnal Ketopong Pendidikan, 2025)
The current rapid development of science and technology and the limitations of face-to-face learning during the Covid 19 pandemic, have required online learning. This affects the length of screen time, especially in the early childhood stages. The impact of online learning and increased screen time in early childhood needs to be investigated to become a reference for learning methods and strategies for both teachers and parents. This study was conducted by comparing some of the literature on online learning and screen time in early childhood. This study shows that the positive impact of online learning is that it allows children to be able to learn from anywhere and at any time, increases the time and cost efficiency, and allows children to have a wealth of unique learning experiences. While the negative impacts are the uneven quality of internet connections, especially in remote areas, limited access to learning tools to support online learning processes, limited digital skills of children and teachers, and limited interaction between teachers and children. The side effects of excessive amounts of screen time in early childhood can be detrimental to physical and mental health, causing speech delays, and limiting opportunities to develop social skills.